The role of information alignment and entrepreneurial traits on SME internationalization: A conceptual framework. Issue 2 (15th February 2016) - Peschken, Thomas; Shukla, Paurav; Lennon, John; Rate, Shirley
Abstract : Purpose: – The paper aims to explore the internationalisation decision-making of small- and medium-sized enterprise (SME) owner/managers. Specifically, structural alignment theory (SAT) and regulatory focus theory (RFT) are utilised to examine the concept of opportunity recognition in the context of internationalisation choices. Design/methodology/approach: – This paper is conceptual in nature, and an integrative cognitive model of internationalisation choice decisions is developed based on SAT and RFT, underpinned by a critical review of the international entrepreneurship (IE) literature. Findings: – Scenarios are identified in which the structure of available information may affect the decision-evaluation process in terms of cognitive resource requirements. Further, the SME owner/manager's motivational goal orientation is suggested to moderate the role of the information structure in line with IE literature. A conceptual model and propositions are presented. Research limitations/implications: – The conceptual model and the propositions arising from the discussion in this paper offer new directions of research to explore SME internationalisation. Originality/value: – This paper offers a cognitive perspective of SME internationalisation. This paper offers insights for policymakers, SME owner/managers, practitioners and researchers alike. For internationalisation decisions, this paper highlights the potential impact of the structure of information that is made available to SME owner/managers by industry or policy bodies; further, the moderating influence of motivational goal orientation may inform policy on how information should be presented to SME owner/managers to aid their decision-making.